Pulverization‐Tolerance and Capacity Recovery of Copper Sulfide for High‐Performance Sodium Storage. Issue 12 (26th April 2019) - Park, Jae Yeol; Kim, Sung Joo; Yim, Kanghoon; Dae, Kyun Seong; Lee, Yonghee; Dao, Khoi Phuong; Park, Ji Su; Jeong, Han Beom; Chang, Joon Ha; Seo, Hyeon Kook; Ahn, Chi Won; Yuk, Jong Min
Abstract: Finding suitable electrode materials is one of the challenges for the commercialization of a sodium ion battery due to its pulverization accompanied by high volume expansion upon sodiation. Here, copper sulfide is suggested as a superior electrode material with high capacity, high rate, and long‐term cyclability owing to its unique conversion reaction mechanism that is pulverization‐tolerant and thus induces the capacity recovery. Such a desirable consequence comes from the combined effect among formation of stable grain boundaries, semi‐coherent boundaries, and solid‐electrolyte interphase layers. The characteristics enable high cyclic stability of a copper sulfide electrode without any need of size and morphological optimization. This work provides a key finding on high‐performance conversion reaction based electrode materials for sodium ion batteries. Abstract : Pulverization‐tolerance and the capacity recovery in CuS enable its outstanding cyclic stability without any size or morphological optimization. Semi‐coherent interfaces in conversion reaction relieves sodium insertion‐induced stress by forming stable grain and phase boundaries rather than random pulverization. Generated grain boundaries enlarge active surface area for sodium insertion and extraction for the capacity recovery.